Environment-friendly high-toughness flame-retardant ABS (Acrylonitrile Butadiene Styrene) composition and preparation method and application thereof
By adding specific flame retardant and reinforcement ingredients to the ABS resin, an environmentally friendly high-toughness flame retardant ABS composition is prepared, which solves the problems of flammable and high antimony trioxide costs of ABS resin, and achieves high efficiency flame retardant and excellent mechanical properties, which are suitable for new energy vehicle materials.
Patent Information
- Application Number
- CN202510090522.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing ABS resin materials are flammable and have a low oxygen index, making it difficult to meet the high requirements of new energy vehicles for flame retardant performance and mechanical properties, especially the high cost and difficulty in using antimony trioxide.
An environmentally friendly high-tough flame retardant ABS composition is prepared by adding antimony trioxide, bromotriazine, hexabromobroncyclododecane, HP-AHB flame retardant, anti-drip agent, zinc borate and nano-calcium carbonate to the ABS resin, and the HP-AHB flame retardant is used to replace partial antimony trioxide, reducing costs and improving flame retardant and mechanical properties.
It realizes the efficient flame retardant and excellent mechanical properties of ABS resin materials, reduces costs, and can meet the high requirements of new energy vehicles for materials.
Smart Images

Figure CN119775682A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardants, and in particular to an environmentally friendly high-toughness flame-retardant ABS composition and a preparation method and application thereof. Background Art
[0002] Acrylonitrile-butadiene-styrene copolymer is a terpolymer composed of acrylonitrile, butadiene and styrene, referred to as ABS. It has excellent impact resistance, heat resistance, low temperature resistance, chemical resistance and electrical properties. It is also easy to process, has stable product dimensions, and has good surface gloss. It is easy to paint and color, and can also be subjected to secondary processing such as surface metallization, electroplating, welding, hot pressing and bonding. It is widely used in industrial fields such as machinery, automobiles, electronic appliances, instruments and meters, textiles and construction. It is a thermoplastic with extremely wide applications.
[0003] ABS resin has very good mechanical properties, namely high tensile strength, high tensile modulus, good toughness and excellent wear resistance. However, the oxygen index of ABS resin is only 18-20%, which is flammable, so it is of great significance to improve the flame retardant properties of ABS resin materials.
[0004] At present, the flame retardant commonly used in ABS plastics on the market is bromine antimony flame retardant, which has good flame retardant effect and little degradation of material properties. 2 O 3 ) is a white powder with a melting point of 654°C. It is usually mixed with brominated flame retardants to achieve flame retardant effects. 2 O 3 The price is expensive and rising year by year. The cost of flame-retardant ABS raw materials continues to rise, so the development and application research of high-efficiency, environmentally friendly and low-cost flame retardants is particularly important.
[0005] The core component of new energy vehicles is the power battery system, and the on-board power battery system is generally made of synthetic materials such as functional plastics, which places higher requirements on the flame retardant and mechanical properties of the materials.
[0006] Therefore, a Sb 2 O 3 The technical problem that needs to be solved at this stage is to develop an environmentally friendly, high-toughness, flame-retardant ABS composition with small usage, good flame retardancy and excellent mechanical properties that can meet the application needs of new energy vehicles. Summary of the invention
[0007] In view of this, the present invention provides an environmentally friendly high-toughness flame-retardant ABS composition and a preparation method and application thereof. The environmentally friendly high-toughness flame-retardant ABS composition prepared by the present application has low cost, good flame retardant effect and excellent mechanical properties, and can be applied to the field of new energy vehicles.
[0008] To solve the above problems, the present invention adopts the following technical solutions:
[0009] An environmentally friendly high-toughness flame-retardant ABS composition and a preparation method and application thereof, the method comprising the following steps:
[0010] The invention discloses an environment-friendly high-toughness flame-retardant ABS composition, which is mainly composed of the following raw materials in parts by weight: 2-3 parts of antimony trioxide, 3-6 parts of bromotriazine, 1-3 parts of hexabromocyclododecane, 1-2 parts of HP-AHB flame retardant, 80-85 parts of ABS resin composition, 0.1-0.5 parts of anti-dripping agent, 1-3 parts of zinc borate and 5-10 parts of nano calcium carbonate.
[0011] Furthermore, the environmentally friendly high-toughness flame-retardant ABS composition is mainly composed of the following raw materials in parts by weight: 2.5 parts of antimony trioxide, 5 parts of bromotriazine, 2 parts of hexabromocyclododecane, 1.5 parts of HP-AHB flame retardant, 83 parts of ABS resin composition, 0.3 parts of anti-dripping agent, 2 parts of zinc borate and 7 parts of nano calcium carbonate.
[0012] Furthermore, the HP-AHB flame retardant is obtained by the following method: triethanolamine and ferrous acetate are mixed in a mass ratio of 2-3:1, and then heated to 65-75°C under stirring conditions, followed by adding calcium hydrogen phosphate, magnesium hydrogen phosphate, and zinc phosphate, and continuing to heat to 80-85°C under stirring conditions, and keeping warm for 3-5 hours to obtain the HP-AHB flame retardant.
[0013] Furthermore, the mass ratio of the calcium hydrogen phosphate, magnesium hydrogen phosphate and zinc phosphate is 2-4:2:1.
[0014] Furthermore, the ABS resin composition is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 60-65:35-40.
[0015] Furthermore, the ABS resin composition is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 65:35.
[0016] Furthermore, the average particle size of the SAN resin is 200-300 nm, and the average particle size of the high-rubber powder is 100-150 nm.
[0017] The present application also provides a method for preparing the above-mentioned environmentally friendly high-toughness flame-retardant ABS composition, which comprises the following steps: uniformly mixing antimony trioxide, bromotriazine, hexabromocyclododecane, HP-AHB flame retardant, ABS resin composition, anti-dripping agent, zinc borate and nano-calcium carbonate, granulating with an extruder, and making plastic strips with an injection molding machine to obtain the environmentally friendly high-toughness flame-retardant ABS composition.
[0018] The composite material of the present application has the characteristics of high toughness and good flame retardant effect, and can be used in the field of new energy vehicles.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention provides an environmentally friendly high-toughness flame-retardant ABS composition. A flame-retardant component and a reinforcing component are added to the ABS resin composition. The ABS composition finally obtained has the characteristics of good flame retardancy and excellent mechanical properties, and can be applied to the field of new energy vehicles.
[0021] 2. Based on the problem that ABS is extremely flammable and has a low limiting oxygen index, the present invention compounded bromine flame retardants and antimony trioxide and other ingredients to improve flame retardancy. However, antimony trioxide is expensive and difficult to obtain. The applicant further developed an HP-AHB flame retardant that can replace part of antimony trioxide. Adding HP-AHB flame retardant to the system can play a flame retardant role in both gas phase and condensed phase. When the polymer burns, PO· can be decomposed, which plays a flame retardant role in the gas phase, and generates phosphorus-containing low-activity substances, which promote the formation of a dense carbon layer in the condensed phase to achieve flame retardancy in the condensed phase. Moreover, it has a good synergistic flame retardant effect with bromine antimony flame retardant, and can partially replace antimony trioxide to reduce the amount of antimony trioxide used in the system, thereby reducing costs while ensuring flame retardant properties. In addition, the applicant unexpectedly found that after the HP-AHB flame retardant prepared by the present application replaces part of antimony trioxide, the environmentally friendly high-toughness flame retardant ABS composition has better mechanical properties.
[0022] 3. The ABS resin composition of the present invention is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 65:35. Both the SAN resin and the high-rubber powder are powdery and have a small particle size. It is found in experiments that the ABS resin composition obtained by mixing the SAN resin and the high-rubber powder in the above ratio can enhance the mixing effect between the raw materials, thereby improving the quality of the finished product. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the electron microscope image of the eighth group of materials in the test example;
[0024] Figure 2 This is an electron microscope image of the flame retardant ABS composition obtained in Example 2. DETAILED DESCRIPTION
[0025] The following embodiments may help those skilled in the art to more fully understand the present invention, but shall not limit the present invention in any way.
[0026] Example 1
[0027] This embodiment provides an environmentally friendly high-toughness flame-retardant ABS composition, which is mainly composed of the following raw materials in parts by weight: 2 parts of antimony trioxide, 3 parts of bromotriazine, 1 part of hexabromocyclododecane, 1 part of HP-AHB flame retardant, 80 parts of ABS resin composition, 0.1 parts of anti-dripping agent, 1 part of zinc borate and 5 parts of nano calcium carbonate;
[0028] The HP-AHB flame retardant is obtained by the following method: triethanolamine and ferrous acetate are mixed in a mass ratio of 2:1, then heated to 65°C under stirring conditions, and then calcium hydrogen phosphate, magnesium hydrogen phosphate, and zinc phosphate are added in a mass ratio of 2:2:1, and the temperature is continued to be heated to 80°C under stirring conditions. Keep warm for 3 hours to obtain the HP-AHB flame retardant. The ABS resin composition is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 60:45. The average particle size of the SAN resin is 200nm, and the average particle size of the high-rubber powder is 100nm.
[0029] The method for preparing the above-mentioned environmentally friendly high-toughness flame-retardant ABS composition is: according to the above-mentioned weight parts, antimony trioxide, bromotriazine, hexabromocyclododecane, HP-AHB flame retardant, ABS resin composition, anti-dripping agent, zinc borate and nano-calcium carbonate are uniformly mixed, granulated by an extruder, and plastic specimens are made by an injection molding machine to obtain the above-mentioned environmentally friendly high-toughness flame-retardant ABS composition.
[0030] Example 2
[0031] The present embodiment provides an environmentally friendly high-toughness flame-retardant ABS composition, which is mainly composed of the following raw materials in parts by weight: 2.5 parts of antimony trioxide, 5 parts of bromotriazine, 2 parts of hexabromocyclododecane, 1.5 parts of HP-AHB flame retardant, 83 parts of ABS resin composition, 0.3 parts of anti-dripping agent, 2 parts of zinc borate and 7 parts of nano calcium carbonate;
[0032] The HP-AHB flame retardant is obtained by the following method: triethanolamine and ferrous acetate are mixed in a mass ratio of 2:1, then heated to 70°C under stirring conditions, and then calcium hydrogen phosphate, magnesium hydrogen phosphate, and zinc phosphate are added in a mass ratio of 3:2:1, and the temperature is continued to be heated to 82°C under stirring conditions, and kept warm for 4 hours to obtain the HP-AHB flame retardant. The ABS resin composition is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 65:35. The average particle size of the SAN resin is 250nm, and the average particle size of the high-rubber powder is 120nm.
[0033] The method for preparing the above-mentioned environmentally friendly high-toughness flame-retardant ABS composition is: according to the above-mentioned weight parts, antimony trioxide, bromotriazine, hexabromocyclododecane, HP-AHB flame retardant, ABS resin composition, anti-dripping agent, zinc borate and nano-calcium carbonate are uniformly mixed, granulated by an extruder, and plastic specimens are made by an injection molding machine to obtain the above-mentioned environmentally friendly high-toughness flame-retardant ABS composition.
[0034] Example 3
[0035] The present embodiment provides an environmentally friendly high-toughness flame-retardant ABS composition, which is mainly composed of the following raw materials in parts by weight: 3 parts of antimony trioxide, 6 parts of bromotriazine, 3 parts of hexabromocyclododecane, 2 parts of HP-AHB flame retardant, 85 parts of ABS resin composition, 0.5 parts of anti-dripping agent, 3 parts of zinc borate and 10 parts of nano calcium carbonate;
[0036] The HP-AHB flame retardant is obtained by the following method: triethanolamine and ferrous acetate are mixed in a mass ratio of 3:1, then heated to 75°C under stirring, then calcium hydrogen phosphate, magnesium hydrogen phosphate, and zinc phosphate are added in a mass ratio of 4:2:1, and the temperature is continued to be heated to 85°C under stirring, and kept warm for 5 hours to obtain the HP-AHB flame retardant. The ABS resin composition is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 62:38. The average particle size of the SAN resin is 300nm, and the average particle size of the high-rubber powder is 150nm.
[0037] The method for preparing the above-mentioned environmentally friendly high-toughness flame-retardant ABS composition is: according to the above-mentioned weight parts, antimony trioxide, bromotriazine, hexabromocyclododecane, HP-AHB flame retardant, ABS resin composition, anti-dripping agent, zinc borate and nano-calcium carbonate are uniformly mixed, granulated by an extruder, and plastic specimens are made by an injection molding machine to obtain the above-mentioned environmentally friendly high-toughness flame-retardant ABS composition.
[0038] Test example:
[0039] In order to illustrate the effect of this application, the applicant conducted group tests on the flame retardant effect and mechanical properties of each group of products, and the groups are as follows:
[0040] The first group: an environmentally friendly, high-toughness, flame-retardant ABS composition prepared by the method described in Example 2 of the present application;
[0041] Group 2: Remove the HP-AHB flame retardant, use 4 parts of antimony trioxide, and the other methods are the same as Group 1;
[0042] The third group: remove the HP-AHB flame retardant, and the other methods are the same as the first group;
[0043] The fourth group: the average particle size of the SAN resin and high-rubber powder constituting the ABS resin composition is 6 mm, and the other methods are the same as the first group;
[0044] Group 5: The mass ratio of SAN resin to high-rubber powder is 85:15, and the other methods are the same as those of Group 1;
[0045] Group 6: The mass ratio of SAN resin to high-rubber powder is 45:55, and the other methods are the same as those of Group 1;
[0046] Group 7: The environmentally friendly high-toughness flame-retardant ABS composition is mainly composed of the following raw materials in parts by weight: 1.5 parts of antimony trioxide, 5 parts of bromotriazine, 2 parts of hexabromocyclododecane, 2.0 parts of HP-AHB flame retardant, 83 parts of ABS resin composition, 0.3 parts of anti-dripping agent, 2 parts of zinc borate and 7 parts of nano calcium carbonate, and the other methods are the same as those of Group 1;
[0047] Group 8: Control group: ABS resin composition, all of which are SAN resin and high-rubber powder.
[0048] First, compare the vertical burning grades of the above groups. The vertical burning grade test is carried out in accordance with GB / T 2408-2021 standard, and a horizontal vertical burning tester is used to carry out a vertical burning test on the sample. The sample size is 125mm×13mm×2.5mm. During the test, ignite the sample 10mm from the bottom and keep it for 10s before leaving. When the sample is extinguished, continue to ignite it for a second time for 10s. If the extinguishing time after two ignitions is less than 10s and there is no melt droplet to ignite the cotton ball, it passes the V-0 grade; if the extinguishing time after two ignitions is less than 30s and there is no melt droplet to ignite the cotton ball, it passes the V-1 grade; if the extinguishing time after two ignitions is less than 30s, there are burning particles or dripping objects that ignite the cotton ball, it passes the V-2 grade. In addition, there is no burning grade if the time exceeds the specified time or the flame burns to the fixture.
[0049] The basis for judging the vertical burning level is shown in Table 1:
[0050] Table 1 Vertical combustion levels and criteria
[0051]
[0052] The vertical combustion grades and some mechanical properties of each group of products are compared, and the results are shown in Table 2:
[0053] Table 2 Quality comparison of each group of products
[0054]
[0055] According to the results in Table 2, the HP-AHB flame retardant of the present application can replace part of antimony trioxide and improve the economic benefits of the product. In addition, after the HP-AHB flame retardant prepared by the method of the present application replaces antimony trioxide, the mechanical properties of the product are improved. In addition, it is known from the experiment that the composition and morphology of the raw materials in the ABS resin composition also have a great influence on the quality of the product.
[0056] The electron microscope images of the first and eighth groups of products are shown in Figure 2 and Figure 1 As shown in the figure, it can be seen that Figure 1 In the test, the ABS carbon layer is relatively loose and incomplete, and has a large number of loose holes, loose structure, and discontinuity. This incomplete carbon layer has almost no protective effect on the ABS material and basically cannot play a condensed phase flame retardant role;
[0057] Figure 2 The surface of the carbon layer is dense and continuous, and no holes or cracks can be observed on the surface. The continuity and integrity of the carbon layer are improved. The complete and dense carbon layer has a good insulation effect, and has a strong ability to block heat and oxygen. It can prevent the heat of combustion from being transferred to the inner layer, making it difficult for the surrounding materials to heat up; it can also isolate combustible volatiles, so that they cannot provide fuel for the flame, and play a condensed phase flame retardant role. In summary, a dense and continuous carbon layer is formed on the surface of the flame retardant material because the introduction of HP-AHB significantly improves the carbonization ability of ABS, forming a denser carbonization layer, which acts as a barrier to heat flow and gas transport, can reduce the outward diffusion of volatile combustible gases, and plays a role in blocking oxygen exchange and heat exchange, and plays a flame retardant role in the condensed phase.
[0058] In summary, the environmentally friendly high-toughness flame-retardant ABS composition prepared by the method of the present application has the characteristics of good flame retardancy and excellent mechanical properties, and can be applied to the field of new energy vehicles.
[0059] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. An environmentally friendly high-toughness flame-retardant ABS composition, characterized in that: The environmentally friendly high-toughness flame-retardant ABS composition is mainly composed of the following raw materials in parts by weight: 2-3 parts of antimony trioxide, 3-6 parts of bromotriazine, 1-3 parts of hexabromocyclododecane, 1-2 parts of HP-AHB flame retardant, 80-85 parts of ABS resin composition, 0.1-0.5 parts of anti-dripping agent, 1-3 parts of zinc borate and 5-10 parts of nano calcium carbonate.
2. The environmentally friendly high-toughness flame-retardant ABS composition according to claim 1, characterized in that: The environmentally friendly high-toughness flame-retardant ABS composition is mainly composed of the following raw materials in parts by weight: 2.5 parts of antimony trioxide, 5 parts of bromotriazine, 2 parts of hexabromocyclododecane, 1.5 parts of HP-AHB flame retardant, 83 parts of ABS resin composition, 0.3 parts of anti-dripping agent, 2 parts of zinc borate and 7 parts of nano calcium carbonate.
3. The environmentally friendly high-toughness flame-retardant ABS composition according to claim 1, characterized in that: The HP-AHB flame retardant is obtained by the following method: triethanolamine and ferrous acetate are mixed in a mass ratio of 2-3:1, and then the temperature is raised to 65-75°C under stirring conditions, followed by adding calcium hydrogen phosphate, magnesium hydrogen phosphate, and zinc phosphate, and the temperature is further raised to 80-85°C under stirring conditions, and the temperature is kept for 3-5 hours to obtain the HP-AHB flame retardant.
4. The environmentally friendly high-toughness flame-retardant ABS composition according to claim 3, characterized in that: The mass ratio of the calcium hydrogen phosphate, magnesium hydrogen phosphate and zinc phosphate is 2-4:2:
1.
5. The environmentally friendly high-toughness flame-retardant ABS composition according to claim 1, characterized in that: The ABS resin composition is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 60-65:35-40.
6. The environmentally friendly high-toughness flame-retardant ABS composition according to claim 5, characterized in that: The ABS resin composition is obtained by mixing SAN resin and high-rubber powder in a mass ratio of 65:
35.
7. The environmentally friendly high-toughness flame-retardant ABS composition according to claim 5, characterized in that: The average particle size of the SAN resin is 200-300 nm, and the average particle size of the high-rubber powder is 100-150 nm.
8. The method for preparing an environmentally friendly high-toughness flame-retardant ABS composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: uniformly mixing antimony trioxide, bromotriazine, hexabromocyclododecane, HP-AHB flame retardant, ABS resin composition, anti-dripping agent, zinc borate and nano calcium carbonate, granulating with an extruder, and making plastic strips with an injection molding machine to obtain the environmentally friendly high-toughness flame-retardant ABS composition.
9. Application of the ABS composition prepared by the method according to claim 8 in new energy vehicles.
Citation Information
Patent Citations
Flame-retardant ABS composite material
CN110951207A
ABS composite material and preparation method thereof
CN112143162A
Granular compound halogen-free flame retardant as well as preparation method and application thereof
CN116285001A
Thermoplastic resin composition and method for producing the same and molding
JP2019137733A
Cited By
Halogen-free flame-retardant low-smoke ABS composite material and preparation method thereof
CN121086454A
Halogen-free flame-retardant low-smoke ABS composite material and preparation method thereof
CN121086454B